2010
DOI: 10.4314/ajtcam.v7i2.50861
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of extracts of three croton species collected in Mpumalanga region in South Africa

Abstract: The antibacterial activities of three Croton species were compared using bioautography and the serial microdilution methods. The methanolic extracts of all the species had low activity against Escherichia coli. The highest activity was observed with Croton megalobotrys against Enterococcus faecalis with a minimal inhibitory concentration (MIC) value of 0.02 mg/ml. Croton steenkapianus extracts were the least active of the species investigated, only managing an MIC value of 0.625 mg/ml against Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
7
1
2
Order By: Relevance
“…Approximating several antibacterial (Mathabe et al, 2006;Aiyegoro et al, 2008;Selowa et al, 2010) and antifungal activities (Dabur et al, 2007;Sharma et al, 2008;Sati and Joshi, 2011) of plants materials extracted with alcohols were mostly reported, this study indicates that acetone Table 2. Inhibition zones produced by ciprofloxacin and extract against tested bacteria.…”
Section: Discussionmentioning
confidence: 63%
“…Approximating several antibacterial (Mathabe et al, 2006;Aiyegoro et al, 2008;Selowa et al, 2010) and antifungal activities (Dabur et al, 2007;Sharma et al, 2008;Sati and Joshi, 2011) of plants materials extracted with alcohols were mostly reported, this study indicates that acetone Table 2. Inhibition zones produced by ciprofloxacin and extract against tested bacteria.…”
Section: Discussionmentioning
confidence: 63%
“…In similar a study, Selowa and coworkers [27] using extracts of three Croton species ( C. megalobotrys , C. steenkampianus and C. salvaticus ) observed that the methanol extract of C. megalobotrys was the most active extract inhibiting S. aureus at 0.625 mg mL −1 , P. aeruginosa at 0.313 mg mL −1 against and E. coli at 0.125 mg mL −1 . The methanol extracts of C. campestris [28] and C. membranaceus showed antimicrobial activity against S. aureus .…”
Section: Resultsmentioning
confidence: 91%
“… Rubiaceae Unknown Leaf extracts K. pneumoniae MIC = 80 μg/mL Elisha et al (2017) Croton megalobotrys Müll.Arg. Euphorbiaceae Feverberry (English), koorsbessie, grootkoorsbessie (Afrikaans), motsibi (Sotho), muruthu (Venda) Leaf extracts P. aeruginosa MIC = 313 μg/mL Selowa et al (2010) Croton pseudopulchellus Pax Euphorbiaceae Small lavender fever-berry (English), kleinlaventelkoorsbessie, sandkoorsbessie (Afrikaans), uHubeshane (Zulu) Aerial parts extracts M. tuberculosis MIC = 500 μg/mL Lall and Meyer (1999) Croton silvaticus Hochstetter ex Krauss Euphorbiaceae Forest fever berry (English) Leaf extracts P. aeruginosa MIC = 1250 μg/mL Selowa et al (2010) Conyza scabrida DC. Asteraceae Oven bush (English), bakbesembossie, bakbos, oondbos (Afrikaans), Leaf extracts M. tuberculosis MIC = 300 μg/mL Seaman (2005) K. pneumoniae MIC = 2000 μg/mL Cyperus articulatus L. Cyperaceae Jointed flat sedge (English) Root extracts M. smegmatis (model for TB) Inactive York et al (2011) K. pneumoniae MIC = 2670 μg/mL Cryptocarya latifolia ...…”
Section: Resultsmentioning
confidence: 99%